On the Foundation of the ”V. M. Bekhterev Friends’ International Society” - N. G. Neznanov; M. A. Akimenko (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
The article presents information  about the foundation of a new public organization,  the “V. M. Bekhterev Friends’ International Society”, at the V.M. Bekhterev National Research Medical Center for Psychiatry and Neurology with the aim to further extend the study of V.M. Bekhterev’s scientific legacy and to create, on the basis of the Society, the V. M. Bekhterev Encyclopedia.